PERANAN IKATAN NOTARIS INDONESIA DALAM PEMBINAAN NOTARIS DAN PENGAWASAN KODE ETIK NOTARIS DI WILAYAH SUMATERA UTARA - HERLINA ERNAWATI NAPITUPULU (PREMISE LAW JURNAL, 2017)
The Indonesian Notarial Association in developing Notaries and supervision of Notarial Code of Ethics through the Notarial Supervisory Council that has the authority to develop Notary’s moral and ethics by conducting inspection on the violation against the Code of Ethics and imposing sanction on those who violate them. The role of the Indonesian Notarial Association in developing Notaries and supervising notarial code of ethics in North Sumatera is by giving input to the Notarial education to make the balance in notarial education and profession, providing code of ethics test, providing activity in increasing Notaries’ knowledge and morality, providing advocacy and assistance for Notaries who have problems, and imposing sanction on those who violate Notarial Code of Ethics.In implementing notarial development and supervising code of ethics, the Indonesian Notarial Association faces some obstacles: notaries’ population, integrity, indifference, and non-transparency toward organization. Keywords: Developing, Supervising Notarial Code of Ethics, Review Board of the Indonesian Notarial Association